Business simulation through kiosk business: initial results among independent oil palm smallholders - Azhar Ahmad; Ahmad Raflis Che Omar; Norazlan Alias; Mara Ridhuan Che Abdul Rahman; Lokhman Hakim Osman (Penerbit Universiti Kebangsaan Malaysia, 2020)
Majority of oil palm smallholders belongs to the B40 category due to small scale agricultural activities. Oil palm smallholders who depend on oil crops alone will face the risk of diminishing income. Long-term steps need to be taken to ensure that their income is maintained even if the palm oil prices are falling. The only way to cope with the income shortages is through business. Hence, this business simulation used the bottom-up method pioneered by Elmore (1978) and Herjn and Porter (1978). This approach was based on the implementation network at the bottom of the stage. It was also a study of the targeted group through a process of observation together with the process of implementation. This business simulation selected two (2) independent oil-palm smallholders in Teluk Intan, Perak. Selection of the participants was based on the justified details as to identify the type of business that is appropriate to the local geography and identify the needs and wants of the community. Participants were engaged in cash-related businesses such as selling crops (bananas, tapioca and others) and agricultural-based businesses. Participants were given a kiosk to carry out business activities. Meanwhile, researchers provided training facilities, guidance and financial support in helping smallholders become successful entrepreneurs. It was expected that the operation of this project could help smallholders increase their income and this simulation would become a model for other oil palm smallholders.